The blue economy: Case study on oil palm waste management - Aziz, Nurul Syahida; Jamaludin, Roslan (2015)
This project is about at oil palm plantation using the method of the Blue Economy.The main focus of this project is about the Blue Economy which is practices of sustainability by wipe out of waste and pollution, utilizing by-product to add variety and increasing the productivity, and it also give chances jobs to human.For this project it focuses on produces by product, the product will create from the waste that human unthinkable it can create to become the product can uses to human and can increase the economy of country.For this project the researches at palm oil plantation.The interview was about the oil palm and issues of their have on the oil palm plantation.The implementation of the Blue Economy in the industry will help increase their capital and sales, save the world and help to reduce the pollution. In this project the researches about disposal fronds and bunches of oil palm.The disposal is can do the product and the owner of oil palm farm has used way of the blue economy but it not widespread. So that, in this researches can help the owner of oil palm to commercialize their product and can help to growth their economy.